Implementation of character education at SMP Muhammadiyah 16 Lubuk Pakam: an exploration of role strategies and impact - Diajeng Tiara Anjani; Zailani Zailani; Nur Rahmah Amini (Lembaga Riset Mutiara Akbar, 2026)
Character education is crucial in addressing moral decline in the digital age, and character education in religiously based educational institutions plays a strategic role in integrating religious values and social ethics. This study aims to analyze the implementation of character education at SMP Muhammadiyah 16 Lubuk Pakam, focusing on its roles, the strategies employed, and its impact on student behavior. This study employs a descriptive qualitative approach. Data were collected through participatory observation, in-depth interviews with the vice principal for curriculum affairs, teachers, and students, as well as document analysis. The results indicate that the implementation strategies were carried out through three main approaches: modeling, habit formation, and environmental conditioning. The impact of the program was reflected in students’ religious discipline, independence, leadership, and communication ethics. However, the program still faces challenges in the form of environmental and family-related barriers that affect the quality of graduates. This study concludes that program consistency, curriculum refinement, and harmonious synergy among the school, parents, and the surrounding environment are key factors in the successful internalization of character education at SMP Muhammadiyah 16 Lubuk Pakam.